A hybrid broadband analysis approach for surface-wire junctions structures by applying AIM and asymptotic waveform evaluation technique. Issue 2 (22nd January 2016) - Dong, Hai-Lin; Gong, Shu-Xi; Xue, Hui; Wang, Xing; Zhao, Bo; Zhang, Peng-Fei
Abstract : The asymptotic waveform evaluation (AWE) technique is utilized to deal with broadband electromagnetic problems of surface–wire junction geometries in this paper. To ensure the current continuity, triangles-to-segments junction model is used and the Rao–Wilton–Glisson (RWG) and triangular basis functions are used to solve the distributions of current on perfect electric conductor and wire, respectively. Then, the current on surface conductor, wire, and junctions are expanded in a rational function via Padé approximation. The AWE technique needs to store the high-order derivatives of the self-impedance and mutual-impedance matrices of surface–wire, which increase the memory requirements. Thus, the adaptive integral method is employed to reduce memory requirements and to accelerate the matrix-vector multiplications in an iterative solver. Finally, some numerical examples are shown to demonstrate the efficiency and accuracy of the proposed method